2013
DOI: 10.1038/nsmb.2666
|View full text |Cite
|
Sign up to set email alerts
|

A cancer-associated BRCA2 mutation reveals masked nuclear export signals controlling localization

Abstract: Germline mis-sense mutations affecting a single BRCA2 allele predispose humans to cancer. Here, we identify a protein-targeting mechanism disrupted by the cancer-associated mutation, BRCA2D2723H that controls the nuclear localization of BRCA2 and its cargo, the recombination enzyme RAD51. A nuclear export signal (NES) in BRCA2 is masked by its interaction with a partner protein, DSS1, such that point mutations impairing BRCA2-DSS1 binding render BRCA2 cytoplasmic. In turn, cytoplasmic mis-localization of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 57 publications
3
95
0
1
Order By: Relevance
“…S2E and S6). The mutation that we generated in DBD domain does not affect the distribution of BRCA2 protein, which is consistent with the recent publication in (46). The BRCA2 DDBD and BRCA2 DN cells showed only moderate increases in the number of spontaneous chromosomal aberrations (Table 2) and in sensitivity to DNA damage (Figs.…”
Section: Ddbdsupporting
confidence: 78%
“…S2E and S6). The mutation that we generated in DBD domain does not affect the distribution of BRCA2 protein, which is consistent with the recent publication in (46). The BRCA2 DDBD and BRCA2 DN cells showed only moderate increases in the number of spontaneous chromosomal aberrations (Table 2) and in sensitivity to DNA damage (Figs.…”
Section: Ddbdsupporting
confidence: 78%
“…Recently, DSS1 has been reported to target BRCA2 to RPA (Zhao et al 2015), and it functions in the replacement of RPA with RAD51 on resected ssDNA (see the 'Mediator function of BRCA2 in loading of RAD51 onto ssDNA' section below). According to the breast cancer information core database, more than 25% of cancer-associated missense mutations map to the C-terminal region (residues 2500-2850) (Szabo et al 2000), which includes the sequence through which BRCA2 binds to DSS1 (Jeyasekharan et al 2013). Recent analysis of cancer-associated BRCA2 mutations has led to the identification of a nuclear export signal (NES) in the C-terminal region of BRCA2 (Jeyasekharan et al 2013).…”
Section: Dbdmentioning
confidence: 99%
“…According to the breast cancer information core database, more than 25% of cancer-associated missense mutations map to the C-terminal region (residues 2500-2850) (Szabo et al 2000), which includes the sequence through which BRCA2 binds to DSS1 (Jeyasekharan et al 2013). Recent analysis of cancer-associated BRCA2 mutations has led to the identification of a nuclear export signal (NES) in the C-terminal region of BRCA2 (Jeyasekharan et al 2013). The NES is masked by the interaction with DSS1.…”
Section: Dbdmentioning
confidence: 99%
“…Initial studies showed that DSS1 depletion results in the persistence of RAD51 foci at DSBs (Gudmundsdottir et al 2004) and reduces BRCA2 protein levels (Li et al 2006), but failed to define a clear role for DSS1 in HR. Subsequently, DSS1 has been found to be involved in masking a NES in BRCA2 and thereby controlling both BRCA2 and RAD51 nuclear localization (Jeyasekharan et al 2013). New insight suggests also that DSS1 physically interacts with RPA to promote its unloading and its replacement by RAD51 on ssDNA (Zhao et al 2015).…”
Section: :10mentioning
confidence: 99%
“…1): the BRC repeats, which consist of eight conserved motifs of about 35 amino acids (Bork et al 1996, Bignell et al 1997, Wong et al 1997; the DNA-binding domain (DBD) composed of a long helical domain (HD) and three oligonucleotide/ oligosaccharide-binding (OB) folds (Yang et al 2002); and finally the C-terminal TR2 domain (Sharan et al 1997). BRCA2 is a predominantly nuclear protein and its subcellular localization is controlled by two distinct nuclear localization signals (NLSs) (Yano et al 2000) and a masked nuclear export signal (NES) (Jeyasekharan et al 2013). Finally, BRCA2 acts as a hub and recruits several regulatory proteins including RAD51 (Mizuta et al 1997, Sharan et al 1997, Chen et al 1998b, the partner and localizer of BRCA2 (PALB2)/FANCN (Sy et al 2009, Zhang et al 2009a and FANCD2 (Hussain et al 2004), supporting the notion that BRCA2 is a multifunctional protein involved in several biological pathways (Fig.…”
Section: Brca2 Structural and Functional Domainsmentioning
confidence: 99%